Peran Etika Profesidan Profesional Guru dalam Meningkatkan Mutu Pendidikan - Suhariyah Suhariyah; Nana Hendra Cipta; Maulida Dwi Cahya Ningrum; Salaisyah Azzahra Mahmudi; Mumun Munajiah; Sifa; Husnul Hotimah (Jurnal Pendidikan Guru Profesional, 2025)
Teacher professionalism an important foundation in building public trust in quality of educational services in schools, including implementation of professional ethics and teacher professionalism, which are essential foundations for ensuring the educational process runs responsibly and is oriented towards student needs. This study aims to obtain a clearer picture of the extent to which professional ethics and teacher professionalism are implemented, and what factors become obstacles. Method used in this study is a qualitative approach because it allows researchers to understand the reality on ground more comprehensively. Based on  findings obtained, principal and teachers stated ethics as behavior that is mature, wise, has authority, good character, calming, independent, and polite. In addition, the principal and teachers apply ethics in accordance with their profession, namely as a teacher, this can provide an example for elementary students. Therefore, teachers need to be good role models in the way they dress and behave.